(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Energy resources are the engines that drive every economy [1], [4], [14], Therefore, it is necessary to develop their exploitation in a friendlier, environmentally and sustainable way indeed it is a critically needed nowadays. Then, it is necessary to improve efficiency and optimize renewable energy in order that replace polluting energy sources. This work aims to relate the use of forecasting on meteorological variables such as wind speed, wind direction, solar radiation, among others, obtained by mathematical models implemented on computer to forecast energy production in renewable energies plants. It has been implemented and automated one of the most used models by the scientific community in this field, WRF (Weather Research and Forecasting Model). WRF is a next generation mesoscale model, designed to serve as a tool for meteorological research in addition to provide forecasts in operational regime. This research introduce the topic of energy forecast, mainly of renewable energy, focusing on wind and solar energy, basing the study on a better forecasting of meteorological variables in order to use as income in energy production forecast. A case study in two Spanish renewable energy plants is exposed.